Evaluating binding affinity and toxicity profile of GC14 as potential peptide against phosphotransferase system enzyme PtxA of Streptococcus mutans. (MSW Management Journal, 2026)
Background: Streptococcus mutans (S. mutans) is a major etiological agent of dental caries due to its ability to metabolize carbohydrates,produce acids, and form biofilms on tooth surfaces. The phosphotransferase system (PTS), particularly the PtxA protein, plays an important rolein carbohydrate transport and bacterial metabolism, contributing to bacterial survival and virulence. Targeting metabolic proteins usingantimicrobial peptides represents a promising alternative therapeutic strategy to control S. mutans without promoting antibiotic resistance.Methods: In the present study, the antimicrobial peptide GC14 was computationally evaluated for its therapeutic potential against S. mutans.The peptide was analyzed for toxicity using the ToxinPred server and biological activity using the Peptide Ranker tool. Physicochemicalproperties including molecular weight, net charge, hydrophobicity, and isoelectric point were determined using peptide property analysis tools.Structural characteristics were examined using a helical wheel plot. Molecular docking analysis was performed using the HPEPDOCK server toevaluate the interaction between GC14 and the phosphotransferase system protein PtxA. Additionally, protein–protein interaction networkanalysis was performed to understand the biological role of the target protein.Results: The toxicity prediction indicated that GC14 is non-toxic and suitable for biological applications. The peptide showed a high biologicalactivity prediction score, suggesting strong functional potential. Physicochemical analysis revealed that GC14 possesses typical antimicrobialpeptide characteristics, including amphipathic nature and favorable charge distribution. Molecular docking demonstrated strong binding affinitybetween GC14 and the PtxA protein, indicating stable peptide–protein interaction. Protein interaction network analysis showed that PtxA isassociated with multiple metabolic and cellular pathways in S. mutans.Conclusion: Overall, the findings suggest that GC14 is a promising antimicrobial peptide candidate that may inhibit S. mutans by targetingmetabolic pathways through interaction with the PtxA protein. Further experimental studies are required to validate its antimicrobial and antibiofilm activity.